Penggunaan Game Edukasi Ati (Accounting Tour Indonesia) untuk Meningkatkan Hasil Belajar dan Motivasi Belajar Akuntansi Siswa SMK Negeri 1 Salatiga - Cindy Ayu Paembonan; Dwi Iga Luhsasi; Tri Nugroho Budi Santoso (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: This study examines the effectiveness of the implementation of the ATI (Accounting Tour Indonesia) educational game in improving cognitive, psychomotor, and learning motivation outcomes of class X AKL 1 students at SMK Negeri 1 Salatiga. The initial problem showed low learning achievement with an average score of 60.37 and only 23% of students passed the KKM, plus the dominance of low learning motivation reaching 60% due to monotonous conventional teaching methods. The study used the Classroom Action Research (CAR) approach of the Kemmis & McTaggart model which was implemented in two cycles, including the planning, action, observation, and reflection stages. The research subjects were 35 class X AKL 1 students. Data collection techniques included cognitive learning outcome tests, psychomotor observation sheets, and learning motivation questionnaires. Data analysis was carried out descriptively and comparatively between the pre-cycle, cycle I, and cycle II. The results showed that the ATI educational game succeeded in increasing students' active involvement in the learning process, deepening their understanding of accounting concepts through fun interactive simulations, and triggering students' intrinsic motivation. Significant improvements were seen in cognitive learning outcomes, from an average of 60.37 (pre-cycle) to 78.5 (cycle I) and 85.2 (cycle II), with a pass rate of 91%. Psychomotor skills also increased from 65% to 88% in cycle II, while the percentage of students with low motivation dropped drastically from 60% to just 11%. Students were more enthusiastic because ATI presented accounting learning in a contextual manner, such as simulations of journals, ledgers, and balance sheets in the form of virtual adventures. Overall, ATI's educational games proved effective as an innovative medium that supports accounting learning in vocational schools, making it more engaging, relevant, and meaningful. Accounting teachers are recommended to regularly integrate ATI to overcome boredom and improve the quality of vocational school graduates. Keywords: Educational Games; Learning Outcomes; Learning Motivation; Accounting; Vocational School Abstrak: Penelitian ini mengkaji efektivitas penerapan permainan edukasi ATI (Accounting Tour Indonesia) dalam meningkatkan hasil belajar kognitif, psikomotorik, dan motivasi belajar siswa kelas X AKL 1 di SMK Negeri 1 Salatiga. Masalah awal menunjukkan rendahnya capaian belajar dengan rata-rata nilai 60,37 dan hanya 23% siswa lulus KKM, ditambah dominasi motivasi belajar rendah mencapai 60% akibat metode pengajaran konvensional yang monoton. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (PTK) model Kemmis & McTaggart yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian adalah 35 siswa kelas X AKL 1. Teknik pengumpulan data mencakup tes hasil belajar kognitif, lembar observasi psikomotorik, serta kuesioner motivasi belajar. Analisis data dilakukan secara deskriptif komparatif antara pra-siklus, siklus I, dan siklus II. Hasil penelitian menunjukkan bahwa permainan edukasi ATI berhasil meningkatkan keterlibatan aktif siswa dalam proses belajar, memperdalam pemahaman konsep akuntansi melalui simulasi interaktif yang menyenangkan, serta memicu motivasi intrinsik siswa. Peningkatan signifikan terlihat pada hasil belajar kognitif dari rata-rata 60,37 (pra-siklus) menjadi 78,5 (siklus I) dan 85,2 (siklus II), dengan tingkat kelulusan mencapai 91%. Aspek psikomotorik juga naik dari 65% menjadi 88% pada siklus II, sementara persentase siswa dengan motivasi rendah turun drastis dari 60% menjadi hanya 11%. Siswa lebih antusias karena ATI menyajikan pembelajaran akuntansi secara kontekstual, seperti simulasi jurnal, buku besar, dan neraca dalam bentuk petualangan virtual.Secara keseluruhan, permainan edukasi ATI terbukti efektif sebagai media inovatif yang mendukung pembelajaran akuntansi di sekolah kejuruan menjadi lebih menarik, relevan, dan bermakna. Rekomendasi untuk guru mata pelajaran akuntansi adalah mengintegrasikan ATI secara rutin guna meningkatkan konsentrasi peserta didik meningkatkan kualitas lulusan SMK. Kata kunci: Permainan Edukasi; Hasil Belajar; Motivasi Belajar; Akuntansi; SMK